Loose with the Truth: Predicting Deception in Negotiation - Olekalns, Mara (Journal of business ethics, 2007)
Using a simulated, two-party negotiation, we examined how characteristics of the actor, target, and situation affected deception. To trigger deception, we used an issue that had no value for one of the two parties (indifference issue). We found support for an opportunistic betrayal model of deception: deception increased when the other party was perceived as benevolent, trustworthy, and as having integrity. Negotiators’ goals also affected the use of deception. Individualistic, cooperative, and mixed dyads responded differently to information about the other party’s trustworthiness, benevolence, and integrity when deciding to either misrepresent or leverage their indifference issue. Mixed dyads displayed opportunistic betrayal. Negotiators in all-cooperative and all-individualistic dyads used different information in deciding whether to leverage their indifference issues and used the same information (benevolence) differently in deciding whether to misrepresent the value of their indifference issue.